Can Climate Finance Contribute to Gender Equity in Developing Countries?. (21st March 2016) - Wong, Sam
Abstract: Climate finance helps mobilise additional development funds to help developing countries reduce CO2 emissions and local communities adapt to changing climate. Increasingly, however, concerns have been raised about the implications of climate finance on gender equity. Drawing on the 'contextual‐procedural‐distributive' equity framework, this paper conducts an extensive review of literature on forest sequestration, climate‐smart agriculture and disaster management. It indicates that the effectiveness of climate finance is constrained from a lack of awareness of the gender gap in access to land and capital. To maximise the impact of climate finance, it urges policy makers to tackle deeply rooted structural inequalities. © 2016 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.